Can GPs working in secure environments in England re-license using the Royal College of General Practitioners revalidation proposals? - Coomber, Jane; Charlton, Rodger; Thistlethwaite, Jill E.; England, Liz (BioMed Central, 2012)
Background Revalidation for UK doctors is expected to be introduced from late 2012. For general practitioners (GPs), this entails collecting supporting information to be submitted and assessed in a revalidation portfolio every five years. The aim of this study was to explore the feasibility of GPs working in secure environments to collect supporting information for the Royal College of General Practitioners’ (RCGP) proposed revalidation portfolio.